IMPROVING NATIONAL VALUES THROUGH MUSIC - Qo‘ziyev Toyir Asqarovich (Bright Mind Publishing, 2025)
This article explores the significant role of music in instilling national values in younger generations. It analyzes how Uzbek folk songs, maqom traditions, and traditional instruments express values such as patriotism, compassion, ethics, and diligence. Music is presented not only as a source of aesthetic pleasure but also as a means of cultural memory, historical consciousness, and national identity formation. The study also addresses the role of music in fostering social awareness and moral resilience among youth.
Keywords: National values, music education, maqom, folk songs, youth spirituality, cultural heritage, patriotism, musical aesthetic development, moral consciousness, traditional art.